COVID-19 incidence, severity, medication use, and vaccination among dentists: survey during the second wave in Brazil - Rafael R MORAES; Marcos B CORREA; Paulo R MARTINS-FILHO; Giana S LIMA; Flavio F DEMARCO (University of São Paulo, 2022)
Abstract Objective This cross-sectional study with dentists in Brazil assessed the COVID-19 incidence and severity, its vaccination status, and the level of confidence in vaccines in May 2021 (COVID-19 second wave). The medications used to prevent or treat COVID-19, including controversial substances (vitamin D, ivermectin, zinc, and chloroquine), were analyzed. Methodology Dentists were recruited by email and responded to a pretested questionnaire until May 31, 2021. Bivariate and multivariate regression analyses were performed (α=0.05). Prevalence ratios were calculated for the association between professional characteristics and two outcomes: SARS-CoV-2 infection and use of controversial substances. Results In total, 1,907 responses were received (return rate of 21.2%). One third of dentists reported intermediate levels of confidence in the safety and efficacy of COVID-19 vaccines, but 96% had received at least one vaccine dose, mainly CoronaVac. The effect of the pandemic on dental practice was classified as lower/much lower, in comparison with the first wave, by 46% of participants. Moreover, 27% of dentists had already tested positive for SARS-CoV-2 and about 50% had relatives or friends who had been hospitalized or died from COVID-19. At least one medication was used by 59% of participants and 43% used two or more substances. Vitamin D (41%), ivermectin (35%), and zinc (29%) were the most frequent substances. More experienced dentists (≥21 years of professional experience) were 42% more likely to use controversial substances than less experienced dentists. The prevalence of use of controversial substances was 30% higher among dentists with residency or advanced training, such as postgraduate degrees, in comparison with participants holding MSc or PhD degrees. Participants with low confidence in vaccines were 2.1 times more likely to use controversial substances than participants with a very high confidence. Conclusion The results of this study show the high severity of the COVID-19 pandemic in Brazil and raised questions about the use of scientific evidence by dentists in their decision to use controversial substances.